Electronic and electrochemical properties of grid-type metal ion complexes (Fe+2 and Co2+) with a pyridine-pyrimidine-pyridine based bis(hydrazone) (2018)
The synthesis of new grid-type complexes of Co2+ and Fe2+ based on a highly soluble double hydrazone framework is reported. The data obtained from 1H NMR, FT-IR, and elemental analysis indicate that the complexes adopted a grid-like structure. Electronic properties of the metallogrids were analyzed by UV-Vis spectroscopy in chloroform, methanol, and dichloromethane. Additionally, cyclic voltammetry and square wave voltammetry were carried out in N,N-dimethylformamide (DMF). These compounds exhibited two oxidation processes corresponding to the organic ligand and several reductions events, comprising the ligand and metal centers. Furthermore, the interplay between the metal nature and the ligand framework was also studied in detail. These results represent an advancement in the chemistry of metallogrids not only because of the few reports concerning to the electrochemical properties found in the literature, but also for the design of novel hydrazone ligands of high solubility and easy preparation.